Critical role for scaffolding adapter Gab2 in FcγR-mediated phagocytosis - Gu, Haihua (The Rockefeller University Press, 2003)
Grb2-associated binder 2 (Gab2), a member of the Dos/Gab subfamily scaffolding molecules, plays important roles in regulating the growth, differentiation, and function of many hematopoietic cell types. In this paper, we reveal a novel function of Gab2 in Fcγ receptor (FcγR)–initiated phagocytosis in macrophages. Upon FcγR activation, Gab2 becomes tyrosyl phosphorylated and associated with p85, the regulatory subunit of phosphoinositide 3-kinase (PI3K), and the protein–tyrosine phosphatidylinositol Shp-2. FcγR-mediated phagocytosis is severely impaired in bone marrow–derived macrophages from Gab2−/− mice. The defect in phagocytosis correlates with decreased FcγR-evoked activation of Akt, a downstream target of PI3K. Using confocal fluorescence microscopy, we find that Gab2 is recruited to the nascent phagosome, where de novo PI3K lipid production occurs. Gab2 recruitment requires the pleckstrin homology domain of Gab2 and is sensitive to treatment with the PI3K inhibitor wortmannin. The Grb2 binding site on Gab2 also plays an auxiliary role in recruitment to the phagosome. Because PI3K activity is required for FcγR-mediated phagocytosis, our results indicate that Gab2 acts as a key component of FcγR-mediated phagocytosis, most likely by amplifying PI3K signaling in the nascent phagosome.